Jonathan Dayton correspondence - Dayton, Jonathan, 1760-1824.
ALS (1808 October 17; Pittsburgh, Penn.) to Dayton from James Ross relating to the future of the Federalists (Federal Party). Includes typewritten transcript of the letter.
Typewritten transcript, in part.
Delegate to the Continental Congress and U.S. senator and representative from New Jersey.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ross, James, -- 1762-1847 -- Correspondence; Federal Party (U.S.); United States -- Politics and government -- 19th century; Delegates, U.S. Continental Congress -- New Jersey; Representatives, U.S. Congress -- New Jersey; Senators, U.S. Congress -- New Jersey